Planktonic foraminiferal biostratigraphy and microfacies analysis of the cenomanian-campanian succession in the Haymana-Polatlı Basin (Ankara, Turkey) - Sarıaslan, Nisan (Middle East Technical University, 2017)
In order to establish the planktonic foraminiferal biostratigraphy of the Cenomanian- Campanian deposits in the Haymana-Polatlı Basin, a stratigraphic section of 93.5 meters was measured and 75 samples were collected. The stratigraphic section starts with limestones containing late Cenomanian rotaliporid and dicarinellid species and continues with early-middle Turonian aged clayey limestones with sporadic shale beds. These units are overlain by red colored Santonian limestones and shales containing abundant globotruncanids. The stratigraphic section ends with monotonous grey colored silty shales of the Campanian, whose silt content increases more towards the upper part. vi At the end of detailed taxonomic studies performed on both the washed material and thin sections of the samples, the distributions of planktonic foraminifera throughout the stratigraphic section were determined. Based on these findings, a biostratigraphic framework including 9 biozones and 2 subzones was established. In ascending order, the Rotalipora cushmani Zone - Dicarinella algeriana Subzone, Whiteinella archaeocretacea Zone, Helvetoglobotruncana helvetica Zone, Dicarinella asymetrica Zone - Globotruncanita elevata-Dicarinella asymetrica concurrent range Subzone, Globotruncanita elevata Zone, Globotruncana ventricosa Zone, Globotruncanella spp. Zone, Globotruncana aegyptiaca Zone and Gansserina gansseri Zone were identified. Moreover, the evolution of depositional environment reflected by the changing microfacies types through the stratigraphic section was revealed. The microfacies identified from bottom to top were Planktonic Foraminiferal Packstone, Radiolarian Packstone, Packstone with Planktonic Foraminifera and Radiolaria, Radiolaria-bearing Spiculite Packstone, Planktonic Foraminiferal Wackestone, Wackestone with Planktonic Foraminifera and Radiolaria, Silty Wackestone-Mudstone with Planktonic Foraminifera and Wackestone-Mudstone. The inability to determine the zones representing the late Turonian-Coniacian as well as the ...